Identificación de regiones génicas candidatas para resistencia múltiple a enfermedades de espiga en maíz - Montenegro, Lucía Daniela; Baricalla, Agustín Ariel; Perdomo, Santiago I.; Iglesias, Juliana (Asociación de Ingenieros Agrónomos del Norte de la Provincia de Buenos Aires, 2024)
Maize ears are regularly infected with Fusarium verticillioides (FV), Fusarium graminearum (FG) and Ustilago maydis (UM), which causes reduction of grain yield and quality. However, conventional breeding can be hampered by the complex genetic architecture of disease resistance. In this regard, Genome Wide Association Study (GWAS) based on genotype (SNP)-phenotype association, is effective to identify disease resistance QTLs. The objective of this work was to identify genomic regions associated to multiple disease resistance (MDR) to FV, FG and UM, in a panel of 63 maize inbred lines from the EEA INTA Pergamino Maize Breeding Program, through a GWAS study. Trials for phenotypic evaluation were planted in two environments for FV and FG and in five environments for UM. Genotyping was based on Illumina® MaizeSNP50 BeadChip. Best linear unbiased estimator (BLUE) of the phenotypic data were obtained. Linkage disequilibrium and association analysis were performed by TASSEL. Four candidate bins were obtained for resistance to FV, 10 bins to FG and 7 bins to UM. In particular, bins 2.05 and 2.09 were associated with MDR. The results obtained include genes involved in pathogen recognition and signaling pathways for disease resistance. This work describes for the first time candidates genes associated to MDR in Argentinian germplasm.